Terapi Hipnosis Untuk Mencegah Depresi Post Partum - Asta Adyani (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: The purpose of this study was to analyze the effect of hypnosis on primiparous tendency postpartum depressionMethods: The study design was a non-randomized group pretest-posttest design. Samples are 24 people primiparous mothers consisting of 12 people who were given hypnotherapy group and 12 people are not given hypnotherapy group. Sampling was done by quota sampling. The research was conducted on two places, namely Puskesmas Tanah Kalikedinding. The instrument used to measure postpartum depression using the Edinburgh Postnatal Depression Scale (EPDS), which has been modified by Soep.Results: Results obtained chi square test p = 0.015 (<0.005) indicating effect of hypnosis on tendency postpartum depression in mothersConclusion: There is an influence of hypnosis on the tendency of postpartum depression in primipara mothers at the Puskesmas tanak Kali Kedinding Surabaya